CalPen (Calculator of Penetrance), a web-based tool to estimate penetrance in complex genetic disorders - Addepalli, Aditya; Kalyani, Sakhare; Singh, Minali; Bandyopadhyay, Debashree; Naga Mohan, K. (PloS one, 2020)
Mutations conferring susceptibility to complex disorders also occur in healthy individuals but at significantly lower frequencies than in patients, indicating that these mutations are not completely penetrant. Therefore, it is important to estimate the penetrance or the likelihood of developing a disease in presence of a mutation. Recently, a method to calculate penetrance and its credible intervals was developed on the basis of the Bayesian method and since been used in literature. However, in the present form, this approach demands programming skills for its utility. Here, we developed 'CalPen', a web-based tool for straightforward calculation of penetrance and its credible intervals by entering the number of mutations identified in controls and patients, and the number of patients and controls studied. For validation purposes, we show that CalPen-derived penetrance values are in good agreement with the published values. As further demonstration of its utility, we used schizophrenia as an example of complex disorder and estimated penetrance values for 15 different copy number variants (CNVs) reported in 39,059 patients and 55,084 controls, and 145 SNPs reported in 45,405 patients and 122,761 controls. CNVs showed an average penetrance of 7% with 22q11.21 CNVs having highest value (~20%) and 15q11.2 deletions with lowest value (~1.4%). Most SNPs, on the other hand showed a penetrance of 0.7% with rs1801028 having the highest penetrance (1.6%). In summary, CalPen is an accurate and user-friendly web-based tool useful in human genetic research to ascertain the ability of the mutation/ variant to cause a complex genetic disorder.